2014
DOI: 10.1007/s11856-014-0020-8
|View full text |Cite
|
Sign up to set email alerts
|

Linear semigroups with coarsely dense orbits

Abstract: Abstract. Let S be a finitely generated abelian semigroup of invertible linear operators on a finite dimensional real or complex vector space V . We show that every coarsely dense orbit of S is actually dense in V . More generally, if the orbit contains a coarsely dense subset of some open cone C in V then the closure of the orbit contains the closure of C. In the complex case the orbit is then actually dense in V . For the real case we give precise information about the possible cases for the closure of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…We will obtain more precise information about the closure of the orbit Sx in [1]. In particular we will prove that Gx is dense in V for the complex case, which implies the following.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…We will obtain more precise information about the closure of the orbit Sx in [1]. In particular we will prove that Gx is dense in V for the complex case, which implies the following.…”
Section: Introductionmentioning
confidence: 82%
“…In a forthcoming paper [1] we will give more precise information on the closure of Sx, if Sx is somewhere dense. It is a union of convex cones of a very special type.…”
Section: Applications To Finitely Generated Hypercyclic Abelian Semig...mentioning
confidence: 99%
See 1 more Smart Citation
“…Coarsely dense orbits appear naturally by looking at perturbations of a dense orbit by a vector with bounded orbit [13]. In [1] we studied, together with H. Abels, a similar problem for finitely generated abelian subsemigroups of GL(V ), where V is a finite dimensional complex (or real) vector space. We showed that if such a semigroup has a coarsely dense orbit on an open cone of V then, for the complex case, this orbit is actually dense in V .…”
Section: Introduction and Basic Conceptsmentioning
confidence: 99%